The Effect Of Stock Investment Management On Economic Growth In Indonesia - Sucipto, Ahmad; Tarigan, Heskyel Pranata (Utami Publisher, 2025)
Investment management is the art and science of managing financial assets to generate optimal returns, while still considering risks and financial goals. The effect of stock investment management on economic growth in Indonesia, with a focus on the role of digital stock investment applications in increasing domestic investor participation and its impact on the national economy. This study uses a qualitative descriptive approach with secondary data from reports from the Financial Services Authority (OJK), the Central Statistics Agency (BPS), and the Indonesia Stock Exchange (IDX). The results of the study show that the volume of stock transactions on the Indonesia Stock Exchange has increased significantly from 2019 to 2021, with an average daily transaction volume reaching 424,704 million shares in 2021. The number of domestic investors has also increased, with an average total assets of IDR 140.29 trillion in 2021. This increase was driven by education and literacy programs provided by securities companies digital investment applications. Effective stock investment management through digital platforms contributes to an increase in the number of investors, which in turn increases stock transactions and has a positive impact on the Indonesian economy.